Preparedness for tobacco control among postgraduate residents of a medical college in Bangalore - Prem K Mony; Sylvia Jayakumar (Wolters Kluwer Medknow Publications, 2011)
Background: Tobacco use is a major cause of avoidable mortality. Postgraduate doctors in training are an important group of physicians likely to influence patients' tobacco use/cessation. Objective: To assess preparedness for tobacco control among clinical postgraduate residents of a medical college in southern India. Materials and Methods: A cross-sectional study was undertaken among all clinical postgraduate residents enrolled in St. John's Medical College, Bangalore, to assess knowledge, attitude, and practice regarding tobacco cessation in their patients. A self-administered, anonymous questionnaire was used. Simple descriptive analysis was undertaken. Results: The overall response rate was 66% (76/116). Mean (S.D.) knowledge score on tobacco use prevalence and disease burden was 6.2 (2.0) out of 10. About 25% of them were not aware of nicotine replacement therapy as a treatment option for tobacco cessation. Nearly two thirds of them expected their patients to ask for assistance with quitting and nearly half were sceptical about patients' ability to quit. While 80% of them enquired routinely about tobacco use in their patients, only 50% offered advice on quitting and less than a third assessed readiness to quit or offered assistance with quitting in their patients. Conclusion: Our study revealed suboptimal levels of knowledge and tobacco cessation practice among postgraduate residents. Attitudes toward tobacco cessation by their patients was however generally positive and there was substantial interest in further training in tobacco control. Reorienting postgraduate medical education to include tobacco control interventions would enable future physicians to be better equipped to deal with nicotine addiction.